2022
DOI: 10.1007/s00520-022-06853-6
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and perceptions of social eating for patients living with and beyond head and neck cancer: a qualitative study

Abstract: Purpose Patients with head and neck cancer (HNC) describe eating as more than a physical activity for nutrition and calories. After treatment for HNC, patients report a changed social experience around food, with eating and drinking in front of family and friends depicted as a challenge. However, there is limited research exploring how patients with HNC adapt and cope with social eating difficulties. This study aims to explore patients’ experiences and perceptions of social eating and drinking fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…A thematic guide has been developed and iterated to re ect the research objective [22]. Four pilot interviews were conducted with gynecological cancer survivors to check for doubtful or ambiguous content, so few changes were made to improve the interpretation of the questions.…”
Section: Data Collectionmentioning
confidence: 99%
“…A thematic guide has been developed and iterated to re ect the research objective [22]. Four pilot interviews were conducted with gynecological cancer survivors to check for doubtful or ambiguous content, so few changes were made to improve the interpretation of the questions.…”
Section: Data Collectionmentioning
confidence: 99%
“…This qualitative descriptive study [17] with FMs was part of a broader research project on the experiences of social eating after HNC treatment with three stakeholder groups: patients [10] relatives and healthcare professionals (HCPs). This study is reported according to the Consolidated Criteria for Reporting Qualitative Research (COREQ) guidelines [18].…”
Section: Designmentioning
confidence: 99%
“…Inclusion and exclusion criteria were established, displayed in Table 1. FMs were recruited in two ways: (1) patients with HNC who participated in interviews of the corresponding study [10] were asked if they had a FM who would like to participate and (2) alternatively, HNC Clinical Nurse Specialists (CNSs) from three participating healthcare sites in the UK, who were local collaborators for the research, identified potential FMs and sought permission for the researcher (MD) to contact interested participants to extend a research invitation. The study did not require both patients with HNC and FMs to participate.…”
Section: Sampling and Samplementioning
confidence: 99%
See 2 more Smart Citations